Pengaruh Aktifitas Fisik (Pemijatan) Terhadap Penurunan Tekanan Darah pada Lansia Yang Mengalami Hipertensi di PSTW “Meci Angi” Kota Bima - Chandra Irawan; Musmuliadin Musmuliadin; Eka Rudy Purwana; Ade Saputra (Pusat riset dan Inovasi Nasional, 2025)
Hypertension is one of the major health problems frequently experienced by the elderly and can lead to serious complications if not properly managed. Simple physical activities such as massage can serve as a non-pharmacological intervention to help reduce blood pressure. This study aimed to determine the effect of physical activity in the form of massage on reducing blood pressure in elderly individuals with hypertension at PSTW